Immunomodulatory Effects of Lycii Radicis Cortex Water Extract on Lipopolysaccharide-Activated RAW 264.7 Mouse Macrophages - Wansu Park, (Journal of Pharmacy and Nutrition Sciences, 2014)
The root bark of Lycium chinense Miller (Solanaceae), also known as Lycii radicis cortex, is one of famous plant-originated drugs in Korean medicine owing to its anti-tussive, anti-asthmatic, and antipyretic properties. In this study, the effect of Lycii radicis cortex water extract (LRC; 10 - 200μg/mL) on inflammatory mediators from lipopolysaccharide (LPS)-activated RAW 264.7 mouse macrophages was inspected. After 24 h incubation with LRC, cell viability, nitric oxide (NO), and various cytokines from RAW 264.7 were measured. LRC increased the cell viability of RAW 264.7 at concentrations of up to 200 μg/mL. LRC significantly inhibited the production of NO, granulocyte colony-stimulating factor (G-CSF), tumor necrosis factor-α (TNF-α), platelet derived growth factor-BB (PDGF-BB), interleukin (IL)-2, and IL-10 in LPS-activated RAW 264.7 (P < 0.05). As well, LRC diminished the production of granulocyte-macrophage colony-stimulating factor (GM-CSF) and lipopolysaccharide-induced CXC chemokine (LIX). The current results suggest that LRC has immunomodulatory property to alleviate excessive immune reactions during the activation of macrophages by LPS.